1997
DOI: 10.1056/nejm199707313370503
|View full text |Cite
|
Sign up to set email alerts
|

End-Tidal Carbon Dioxide and Outcome of Out-of-Hospital Cardiac Arrest

Abstract: An end-tidal carbon dioxide level of 10 mm Hg or less measured 20 minutes after the initiation of advanced cardiac life support accurately predicts death in patients with cardiac arrest associated with electrical activity but no pulse. Cardiopulmonary resuscitation may reasonably be terminated in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
157
1
13

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(182 citation statements)
references
References 43 publications
4
157
1
13
Order By: Relevance
“…The median ETCO 2 value of 35 torr in this study mirrors mean ETCO 2 levels in survivors in prior studies, which ranged from 31 torr to 33 torr. 11,13 In comparison with previous studies in which nonsurvivors had mean ETCO 2 levels ranging from 4.4 torr to 20.6 torr, nonsurvivors in our study had a median ETCO 2 level of 13.7 torr.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…The median ETCO 2 value of 35 torr in this study mirrors mean ETCO 2 levels in survivors in prior studies, which ranged from 31 torr to 33 torr. 11,13 In comparison with previous studies in which nonsurvivors had mean ETCO 2 levels ranging from 4.4 torr to 20.6 torr, nonsurvivors in our study had a median ETCO 2 level of 13.7 torr.…”
Section: Discussionmentioning
confidence: 43%
“…7,11,14 Our capnography results (Table 1) add to this evidence base by demonstrating that higher ETCO 2 values are associated with better prognosis. Median ETCO 2 for survivors (35 torr) was significantly higher than for nonsurvivors (13.7 torr).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Among patients in the CARES database, survival after asystole was 2.3%, after pulseless electrical activity 7.4%, and after ventricular arrhythmias, survival was 27.1% 7. Other studies have shown survival to hospital discharge after asystole and pulseless electrical activity to be 2% and 11%, respectively, and survival to hospital discharge among those with VT/VF as high as 40% 22, 23, 24, 25. Among 12 000 patients in Seattle, survival after a cardiac arrest with VF was nearly 10 times higher than among those without VF 24.…”
Section: Prognosis After Sudden Cardiac Arrestmentioning
confidence: 95%
“…[3,48] ETCO 2 'nin KPR sırasında uzun süre 10 mmHg altında kalması SDGD pek olası olmadığı anlamını taşır. [49][50][51][52][53] ETCO 2 'nin sağ-kalım hakkında fikir verip veremeyeceğini değerlendiren iki çalışmanın ilkinde 10 mmHg' nın altında ETCO 2 değeri olan 127 olgudan sadece biri, [54] ikinci çalışmada ise 139 olgudan hiç biri sağ kalmamıştır. [51] Bir başka çalışmada ETCO 2 değeri-nin, KPR prognozunu değerlendirmede kardiyak sonografiye göre daha üstün olduğu saptanmıştır.…”
Section: Kpr Etkinliğinin Değerlendirilmesiunclassified